Meta‐analyses and effect sizes in applied behavior analysis: A review and discussion. Issue 4 (5th July 2021) - Dowdy, Art; Peltier, Corey; Tincani, Matt; Schneider, W. Joel; Hantula, Donald A.; Travers, Jason C.
Abstract : For more than four decades, researchers have used meta‐analyses to synthesize data from multiple experimental studies often to draw conclusions that are not supported by individual studies. More recently, single‐case experimental design (SCED) researchers have adopted meta‐analysis techniques to answer research questions with data gleaned from SCED experiments. Meta‐analyses enable researchers to answer questions regarding intervention efficacy, generality, and condition boundaries. Here we discuss meta‐analysis techniques, the rationale for their adaptation with SCED studies, and current indices used to quantify the effect of SCED data in applied behavior analysis.